2012
DOI: 10.5714/cl.2012.13.1.051
|View full text |Cite
|
Sign up to set email alerts
|

Bridge effect of carbon nanotubes on the electrical properties of expanded graphite/poly(ethylene terephthalate) nanocomposites

Abstract: In this work, expanded graphite (EG)-reinforced poly(ethylene terephthalate) (PET) nanocomposites were prepared by the melt mixing method and the content of the EG was fixed as 2 wt%. The effect of multi-walled carbon nanotubes (MWCNTs) as a co-carbon filler on the electrical and mechanical properties of the EG/PET was investigated. The results showed that the electrical and mechanical properties of the EG/PET were significantly increased with the addition of MWCNTs, showing an improvement over those of PET pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Li et al [8] reported the effect of exfoliation and ultraviolet (UV)/ozone treatment of graphite on the conductivity of xGnP/ epoxy composites, and the effect of hybrid CNT and xGnP particles on the mechanical and electrical properties of epoxy nanocomposites [9]. Kalaitzidou et al [10] stressed the potential use of xGnP as a reinforcement to produce multifunctional polymer composites.…”
Section: Preparation Of Xgnp-coated Carbon Fibers and Carbon Fiber/phenolic Matrix Compositesmentioning
confidence: 99%
“…Li et al [8] reported the effect of exfoliation and ultraviolet (UV)/ozone treatment of graphite on the conductivity of xGnP/ epoxy composites, and the effect of hybrid CNT and xGnP particles on the mechanical and electrical properties of epoxy nanocomposites [9]. Kalaitzidou et al [10] stressed the potential use of xGnP as a reinforcement to produce multifunctional polymer composites.…”
Section: Preparation Of Xgnp-coated Carbon Fibers and Carbon Fiber/phenolic Matrix Compositesmentioning
confidence: 99%
“…Thus, the fourth valence electron remains free in each unit, and these free electrons are delocalized over all atoms and contribute to the electrical nature of CNTs. Thus, CNTs can be conducting or semi-conducting types depending on the type of chirality [25][26][27][28][29][30][31][32][33][34][35][36][37] Semiconducting SWNTs are usually in the form of p-type semiconductors [38]. MWNTs are composed of many tubes of SWNTs and therefore are not likely to be strictly one-dimensional conductors.…”
Section: Electronic Nature Of Cntsmentioning
confidence: 99%
“…According to previous studies of MWCNT/ polymer composites, the percolation thresholds for electrical conductivity were 1-5 wt% MWCNT [11,12] by simple mixing. To reduce the MWCNT content needed in composites, a variety of methods (e.g., processing, modifications, and immiscible blending) have been attempted [4,[13][14][15]. To achieve the required properties, however, several technical issues should be resolved.…”
Section: Melt Extrusionmentioning
confidence: 99%